Legality and Existence of Mambaul Ulum Islamic Boarding School in Korek Village, Kubu Raya Regency - Ahmad Muafi; Rini (INCARE, International Journal of Educational Resources, 2026)
This research effort aims to examine the legal status and operational existence of the Mambaul Ulum Islamic Boarding School, located in Korek Village, Kubu Raya Regency, within the framework of social dynamics and national education policies, especially following the implementation of Law Number 18 of 2019 related to Islamic Boarding Schools. The investigation used a descriptive qualitative methodology, utilizing field research techniques that included observational analysis, comprehensive interviews, and documentation from caregivers, institutional centers, alumni, and the surrounding community. The findings show that the legal recognition of Islamic boarding schools has a major influence on the fortification of institutional frameworks, the management of educational processes, as well as the improvement of a more structured and integrated learning experience that bridges traditional and formal curricula. Instead, the persistence of boarding schools is enforced through the proactive involvement of students, who serve as guardians of Islamic values, traditions, and adaptation to contemporary progress. These results support the assertion that the interaction between formal legal recognition and the cultural resilience of Islamic boarding schools is an important determinant in maintaining their relevance and survival in the face of complex social transformations.